Information system interoperability maturity model - Anggoro, Bayu Koen; Hubeis, Musa; Sailah, Illah (Association for Scientific Computing Electrical and Engineering, 2018)
Management of higher education (HE) cannot run if not yet have technological resources that can meet the needs of the campus community and stakeholders. The focus of this research was to look beyond the use of information systems (IS) of universities in Kopertis III Jakarta on the maturity level of data interoperability, software, communication, and physical IS. Using the Information System Interoperability Maturity Model (ISIMM), this study resulted in an average level of university located at level 3 (Collaborative) indicating the relationship between data was wider to facilitate IS, logical data model was shared and used in the data exchange process and no separation or the data sharing impacts on the easy exchange of information. The optimization of IS interoperability attributes (ease of access), develops ISIMM-based roadmap IS (planning), determines the main problem solving target (improvement), and improves the quality of IS based on importance level were some suggestions that university managers can make in order to advance IS.